Occupying a flat subpocket in a tRNA-modifying enzyme with ordered or disordered side chains: Favorable or unfavorable for binding?. Issue 20 (15th October 2016) - Neeb, Manuel; Hohn, Christoph; Ehrmann, Frederik Rainer; Härtsch, Adrian; Heine, Andreas; Diederich, François; Klebe, Gerhard
Graphical abstract: Abstract: Small-molecule ligands binding with partial disorder or enhanced residual mobility are usually assumed as unfavorable with respect to their binding properties. Considering thermodynamics, disorder or residual mobility is entropically favorable and contributes to the Gibbs energy of binding. In the present study, we analyzed a series of congeneric ligands inhibiting the tRNA-modifying enzyme TGT. Attached to the parent lin -benzoguanine scaffold, substituents in position 2 accommodate in a flat solvent-exposed pocket and exhibit varying degree of residual mobility. This is indicated in the crystal structures by enhanced B-factors, reduced occupancies, or distributions over split conformers. MD simulations of the complexes suggest an even larger scatter over several conformational families. Introduction of a terminal acidic group fixes the substituent by a salt-bridge to an Arg residue. Overall, all substituted derivatives show the same affinity underpinning that neither order nor disorder is a determinant factor for binding affinity. The additional salt bridge remains strongly solvent-exposed and thus does not contribute to affinity. MD suggests temporary fluctuation of this contact.